2016
DOI: 10.22260/isarc2016/0070
|View full text |Cite
|
Sign up to set email alerts
|

A Cloud-Based BIM Platform for Information Collaboration

Abstract: A cloudbased BIM platform for information collaboration Original CitationMa, Ling and Sacks, Rafael (2016) A cloudbased BIM platform for information collaboration. In: 2016 Proceedings of the 33rd ISARC. ISARC, pp. 581589.This version is available at http://eprints.hud.ac.uk/id/eprint/31383/ The University Repository is a digital collection of the research output of the University, available on Open Access. Copyright and Moral Rights for the items on this site are retained by the individual author and/or other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It is well known that BIM supports a platform approach (Farr et al, 2014;Gu et al, 2008;Ma and Sacks, 2016;Singh et al, 2011). However, most are project-level platforms and few span sectors and multiple projects.…”
Section: Concept Of Bim-enabled P-dfmamentioning
confidence: 99%
“…It is well known that BIM supports a platform approach (Farr et al, 2014;Gu et al, 2008;Ma and Sacks, 2016;Singh et al, 2011). However, most are project-level platforms and few span sectors and multiple projects.…”
Section: Concept Of Bim-enabled P-dfmamentioning
confidence: 99%
“…Our work shares much of the motivation and some implementation decisions with three recent publications that have proposed, or used, MongoDB for implementing repositories of BIM models. Ma & Sacks (2016) use MongoDB to store IFC files, motivated by the need for a dynamic data schema: their system uses the IFC schema but also enables dynamic addition of user-defined properties. The authors have demonstrated the use of their system for the task of reconstructing reinforced concrete beam model from earthquake damaged buildings.…”
Section: Related Workmentioning
confidence: 99%
“…Notably, the advanced cloud‐based BIM platforms, like BIM 360, Trimble Connect, and others, can provide a repository of rich data sources about the design stage deserving data mining. But they can only enable users to query data rather than to supplement or evaluate data (Ma & Sacks, 2016). To maximize the strength of the accumulated data in BIM platforms, new network analysis algorithms written in Python can, therefore, be encapsulated in packages and encode in the platforms as the built‐in intelligence, which has better innovation, flexibility, and reliability than software in both qualitative and quantitative SNA and can even achieve real‐time analysis.…”
Section: Introductionmentioning
confidence: 99%